The Palingenesis of Brownfields Through Nature. A comparative case analysis - Piccirillo, Sara; Iodice, Rosaria; Pastena, Benedetta (Contesti. Città, territori, progetti, 2026)
The research proposes a critical reflection on the self-regenerative potential of brownfields thanks to spontaneous rewilding, envisioning them as laboratories of experimentation capable of triggering alternative and adaptive forms of urban regeneration. Guided by the concepts of urban palingenesis, spontaneous ecologies and common goods, the contribution investigates how episodes of prolonged abandonment can cause unexpected processes of ecological rebirth and civic mobilization. A comparative analysis of three emblematic cases - Canvey Wick (UK), La Goccia (Italy) and Bullicante Lake (Italy) - shows how local communities, associations and informal actors can redefine landscapes, functions and values of brownfields. The comparison highlights a constant tension between top-down models of reclamation and bottom-up approaches of care and re-appropriation, suggesting a paradigmatic shift: moving from technical and standardised interventions to open, relational, multi-species and situated processes.